2019
DOI: 10.1088/1361-6463/ab234c
|View full text |Cite
|
Sign up to set email alerts
|

Plasma activated radix arnebiae oil as innovative antimicrobial and burn wound healing agent

Abstract: The plasma enhanced oil based drug, named plasma activated radix arnebiae oil (PARAO) is produced in the radix arnebiae oil (RAO) by a single-step, room temperature, energy-efficient and environment-friendly dry plasma-enabled process. The streamer-surface discharge generates abundant energetic species, atomic oxygen at the plasma-oil interface. The dissociation of C  =  C double bond by energetic species and oxidization by the atomic oxygen is the main mechanism to produce reactive H2O2 and carboxylic acid sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…It is speculated that a small amount of water-soluble carboxylic acid is produced due to the interactions between the plasma and oil. Similar reports have been made by Zou et al [28] and Pan et al [31] Figure 3b shows the electrical conductivity value of the solution with different volumes of oil. The conductivity of the sample with 0 μl oil rises significantly as much as 31.37 μs/cm with the increase of treatment time, while the electrical conductivity of the sample with 50 to 200 μl oil increases slightly.…”
Section: The Physicochemical Properties Of Paowsupporting
confidence: 86%
See 2 more Smart Citations
“…It is speculated that a small amount of water-soluble carboxylic acid is produced due to the interactions between the plasma and oil. Similar reports have been made by Zou et al [28] and Pan et al [31] Figure 3b shows the electrical conductivity value of the solution with different volumes of oil. The conductivity of the sample with 0 μl oil rises significantly as much as 31.37 μs/cm with the increase of treatment time, while the electrical conductivity of the sample with 50 to 200 μl oil increases slightly.…”
Section: The Physicochemical Properties Of Paowsupporting
confidence: 86%
“…It is speculated that a small amount of water-soluble carboxylic acid is produced due to the interactions between the plasma and oil. Similar reports have been made by Zou et al [28] and Pan et al [31] Figure 3b Figure 5 shows the variation of UV absorption spectrum over treatment time in detail. Figure 5a shows the UV absorption spectrum of the solution with 0 μl oil after plasma activation.…”
Section: The Physicochemical Properties Of Paowsupporting
confidence: 85%
See 1 more Smart Citation
“…In approaches of DBD-treated water used for wound healing, positive results on wound healing and antimicrobial efficacy were achieved [ 70 ] that were related to changes in the inflammatory profiles of the wounds [ 71 ]. One further study used gas plasma jet-treated oil emulsion to identify improved wound closure upon application [ 72 ]. A complimentary report applied oil to the wound first, followed by Ar/air or Ar/O 2 plasma jet treatment, also reporting positive results [ 73 ].…”
Section: Gas Plasma Treatment Of Skin and Wounds In Animal And Veterinary Modelsmentioning
confidence: 99%
“…[ 4–6 ] The APPJ has been widely used in material processing, agriculture, nanotechnology, and other fields due to its simple operation and high level of controllability. [ 7,8 ] On the basis of a large number of reactive agents generated by plasma jets in the open environment, such as ultraviolet, charged particles, reactive nitrogen species (RNS) and reactive oxygen species (ROS), [ 9 ] the development of APPJ in biomedicine has become one of the most successful applications, [ 10 ] including sterilization, [ 11 ] wound healing, [ 12 ] root canal treatment, [ 13 ] and cancer treatment. [ 14 ] Although most previous studies have focused on plasma‐induced oxidative and nitrative stress on the treatment objects, our previous studies showed the neuroprotective effect of low‐dose APPJ against different kinds of injuries in vitro, such as oxidative stress, [ 15 ] glucose deprivation, [ 16 ] and hypoxia [ 17 ] ; however, the intracellular targets of APPJ and the mechanisms of the interactions between the APPJ and cells are still unknown.…”
Section: Introductionmentioning
confidence: 99%